Online Business Communication Tools and Their Impact on ESL Curricula - Turgʻunova Shaxzoda Shavkat qizi (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
In recent years, online business communication tools have become very important in professional environments. Applications such as Zoom, Microsoft Teams, and email platforms are widely used for communication in global workplaces. These changes have influenced English as a Second Language (ESL) teaching and learning. This thesis examines how online communication tools affect ESL curricula, especially in terms of communicative competence, digital literacy, and the role of artificial intelligence (AI). The study uses a qualitative approach based on literature review. The findings show that ESL curricula must adapt to modern communication needs by including digital tools and real-life tasks. The study also highlights the importance of teacher training and equal access to technology.